Language and Difference: A Deconstructive Reading Of Niyi Osundare’s “Poetry Is” and Abubakar Othman’s “Wordsworth Lied” - Nureni, Ibrahim; Oluwabukola, Kehinde (LingPoet: Journal of Linguistics and Literary Research, 2021)
The paper examines, using Deconstruction as an analytical framework, the desire by Niyi Osundare and Abubakar Othman to resolve the problematics in and around the composition and reading of poetry in particular and literature in general. The analysis of Osundare’s “Poetry Is” and Othman’s “Wordsworth Lied” demonstrates the ways in which language is not a transparent medium for the representation of truth, knowledge, beliefs since the reading of poetry must scrupulously and tenaciously tease out the point at which the texts differ from themselves. Indeed, language may be a medium through which humans express thoughts, feelings, ideas or forge an identity, but it cannot be reduced to a subjective apprehension. Arguably, the play of difference within language is what makes identity possible and at the same time, thwarts it infinitely. Therefore, the paper concludes with the argument that the two speakers in the selected poems are caught up in self-contradiction or auto-deconstruction, in that there are tensions between what they meant and what the texts say.